Pemanfaatan Jerami Padi Sebagai Media Pertumbuhan dan Hasil Jamur Janggel (Coprinus sp.) Dengan Model Blok Bersusun - Nada Kutsuma Vacha; Agus Sugianto; Anis Sholihah (AGRONISMA, 2021)
Janggel mushrooms are edible fungi / mushrooms that can be consumed and grow on media containing high cellulose, one of which is composted agricultural waste (rice straw), but we do not know for sure the impact of different composting times. This study aims to determine the length of time for composting rice straw media on the growth and yield of janggel mushrooms. The research was conducted at the Agrotechnology Mushroom Cultivation Laboratory, Faculty of Agriculture, Islamic University of Malang From December 2020 to February 2021. The design used was a simple randomized block design (RBD) with 3 replications with a 5% level test, the treatment used was composting time with 5 levels. Namely 0, 3, 6, 9 and 12 days. The results showed that the difference in composting time had a significant effect on the parameters of the diameter of the fruity body hood, the total fresh weight of the fruit body and the period of harvest. However, the composting time of 12 days (L4) showed the highest yield on parameters : the ability of mycelium to fill the media with 6 days after inoculation, and the harvest period with a length of 52 days. However, the 9 day composting time (L3) gave the highest result on the parameter of total fresh weight of the fruit body with a weight of 161.62 grams. However, L2 (6 days of composting) showed the highest yield on the diameter of the fruit body hood with a width of 7.42 mm. The optimum composting time in straw, rice bran and CaCO3 media is 12 days of composting.